Incorporating reflection into computing classes: models and challenges. Issue 3 (4th May 2018) - Chng, Sue Inn
Abstract: Literature has shown that the use of reflective practice is one way to assist students to understand and adjust to the expectations demanded by higher education. However, the implementation of reflective practice within the classroom can be challenging especially more so for the science, technology, engineering and mathematics discipline. It is often the case that reflective exercises are incorporated into the classrooms without further thought beyond the assignment of a reflective journal and students are asked to reflect without being taught how. This paper reviews existing models of reflection and discusses its application to the field of computing education particularly in the design of class activities to train students to reflect. Existing literature on how reflective activities are incorporated into assessments and classroom activities for different purposes are also reviewed to determine factors that contribute to its successful implementation in the classroom.